(untitled) (Italian Review of Legal History, 2021)
The Ladins of Trentino-Alto Adige/Südtirol are an ethnic minority with an ancient history, located in the Dolomites Mountains, a place associated with extreme beauty and rugged land. Under the Italian Constitution, Ladins have acquired several legal rights connected with their language and history. Ladins have a history dating to the Roman Empire. Located in a strategic place, with Alpine valleys and mountain paths that connect the Italian Peninsula with Central Europe, several Germanic tribes after the end of the Roman Empire invaded and established themselves in the zone, enforcing their customs and laws. Those so-called “barbaric laws” together with Carolingian and Ecclesiastical law gave birth to a particular system of law during the Middle Ages. Afterward, Ladins became part of the Holy Roman Empire, and later, part of the House of Habsburg. During the aftermath of World War I, Italy obtained the region from the Austrian-Hungarian Empire in the peace treaty of Saint Germain-en-Laye of 1919. The Italian experience with the Ladins started soon after World War I with several publications taking the task of understanding the origins of their language and its people. Ever since, Italian interest in the Ladins has not ceased. In 1998 the Italian Constitutional Court recognized the Ladin people their right to be represented in regional institutions, answering to the historical and social reality of Alto Adige/Südtirol. Consequently, the legal resilience of the Ladins gives testimony of a long history of peaceful victories for their rights, associated with the Ladin language, in the context of judicial procedures, political participation, and legislation. In comparison, Ladins living in other regions of Italy like Veneto and Friuli Venezia Giulia have not reached the same level of autonomy and privileges as those in Trentino-Alto Adige/Südtirol.